Drug Reaction with Eosinophilia and Systemic Symptoms Associated with a Vancomycin-Impregnated Spacer - Bodendorfer, Blake Michael; Cole, Emily Fahrig; Carstens, Stephanie J.; Sherman, Seth L.; Katta, Natraj (The Journal of Knee Surgery Reports, 2015)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a severe adverse drug reaction with a mortality rate near 10% characterized by erythematous cutaneous eruption, multiorgan involvement, and hypereosinophilia. This case report highlights a patient who developed DRESS in the setting of intravenous vancomycin and a vancomycin and tobramycin-impregnated (PROSTALAC, DePuy Synthes, Warsaw, IN) functional spacer. The spacer was placed during the revision of a left total knee replacement complicated by a septic joint. To our knowledge, this is the third reported case of DRESS associated with vancomycin-impregnated spacers. As DRESS is a potentially life-threatening reaction and the principal treatment is withdrawal of the precipitating drug, it is important to consider this clinical entity and discontinue all forms of the causative agent. Patients with DRESS may develop a diffuse cutaneous eruption, respiratory failure, acute kidney injury, elevated liver enzymes, lymphadenopathy, and/or hemodynamic instability following intravenous infusion of antibiotics or placement of antibiotic-impregnated spacers, beads, or bone cement. Interestingly, this patient had a prominent and progressive erythematous eruption surrounding the left knee that improved after operative removal of the spacer. At 6 week hospital follow-up, the patient's systemic signs and symptoms had essentially resolved.
Keywords: vancomycin; antibiotic spacer; rash; DRESS syndrome